Miłosierdzie chrześcijańskie w nauczaniu i działalności Sługi Bożego ks. Roberta Spiskego założyciela Zgromadzenia Sióstr św. Jadwigi - Michał Dulik (Wrocławski Przegląd Teologiczny)
The Wroclaw-born capitular and founder of the Sisters of Saint Hedwig, and meanwhile servant of God, Spiske, was an “apostle of mercy.” As an outstanding preacher and searched confessor, he belonged to the Catholic renewal movement of the 19th century in the archdiocese of Wroclaw and Prussia. He applied a specific focus of his pastoral activity to the ministry of childern an youth and to the recovery of those believers, who had grown aparat from the Church. In order to give orphans a home, he founded in Wroclaw the congregation of the Sisters of Saint Hedwig. A maxim of his life was: “Without works of mercy you can not be a Christian.” This article demonstrated how he lived this concept concretely. These conditions have been proclaimed by the Church from the beginning. Due to the sacrament of baptism, every Christian is committed to practice the works of mercy in his life. For mature Christians two other sacraments go with these: The sacrament of reconciliation and the eucharist. If oneself receives these two sacraments, wich are given us by God’s compassion, one will be better prepared to render the Christian mercy to other humans; not to forget the prayer.